EFFECTIVENESS OF RUSSIAN ELECTRICAL STIMULATION AND STRENGTHENING EXERCISES IN PATELLOFEMORAL PAIN SYNDROME - Sumit Asthana; Arif Rizvi (Journal of Biomedical and Pharmaceutical Research, 2021)
Background: Patellofemoral Pain Syndrome (PFPS) refers to the clinical presentation of anterior knee pain related to changes in the Patellofemoral joint. Reports of Patellofemoral pain incidence in the clinical environment range from 21% to 40%. It affects as much as 25% of the general non-athletic population and occurs in all age groups and more common among adolescents and young adults. Good clinical results have been shown with quadriceps strengthening, with both open and closed kinetic chain exercises. Also Electrical stimulation is used extensively in physical therapy, and “Russian currents” have been advocated for use in increasing muscle force.Objective: To compare the efficacy of Russian electrical stimulation and Strengthening exercises on pain, disability and VMO strength in PFPS.Study Design: Randomized Control TrialMaterials & Method:30 subjects both male and female, Age group of 18-45 years with PFPS were recruited for study. Strength, Pain and Disability were analyzed in RES and ST groups.Outcome measures were NPRS for pain, 1RM for strength and KPS for disability.Results: Results showed that there is significant improvement Post- RES and ST in both groups.Conclusion: Russian stimulation and Strengthening Exercises were proved to be both effective tool in reducing pain, disability and improving strength of VMO in PFPS patients. Russian stimulation revealed more significant effect in reducing pain and improving VMO strength and strengthening exercises improved the functional outcome of the patients.Keywords: Patello-femoral Pain Syndrome (PFPS), Vastus Medialis Oblique (VMO), Russian Electrical Stimulation (RES), Strength Training/ Strengthening Exercises (ST /SE).